The Effect of Nandralone Decanoate on Athletes Fertility (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Anabolic androgenic steroids (AAS)”, (Nandrolone Decanoate) the treatments most widely abused commonly for improving athletic ability, appearance or muscle mass, athletes, coaches, and physicians should be aware of their harmful side effects .liquorice extract consider important medical plant due to  rich in antioxidants, flavonoids, phenolic and alkaloids that Supports the general  health of the body. In this study we compare between two groups of young athletes from Al-Qassam city, each group contains from six athletes, the first group they taken Nandrolone Decanoate with dose 50 mg, I.M.  for three-time weakly and persistence in a period  at least two months, the second group the without any treatment are using as a control group. The result showing that athletes who taken Nandrolone at least two months there have low elevation in liver enzyme but there are no significant differences in GPT ,GOT, ALP, as well as decreased the levels of mean “serum FSH, LH, and testosterone.